Applications and actions of economic-environmental theoretical approaches in the framework of development - Salas Pinel, Fiorella (2023)
The environment has a fundamental role in the quality of life of the entire globe; on these grounds, this article aims to describe the theoretical evolution of the relationship between economy and environment for the identification of applications and actions within the framework of development. The article takes a methodological approach, which involved an in-depth analytical reading of secondary sources available in websites and sources in print of the main theoretical claims, guided by a qualitative approach and a descriptive type of research, which enabled a series of reflection, dialogue and discussion meetings, firstly among the authors. Subsequently, through a questionnaire or interviews, specialists were consulted on the challenges, opportunities and applications of the different approaches. The research allows to conclude that the evolution of theoretical contributions, from the foundations of Adam Smith’s economic theory to more recent paradigms such as the bioeconomy, evidences a considerable degree of advance in time, which translates into contributions as the instruments for the respective applications and actions overlapped in the development. Additionally, it is possible to indicate that there are important challenges and opportunities for generating and furthering knowledge, as well as practical applications of economic-environmental schemes that potentialize resilience as an essential factor in all human activities.